227 Late-Breaking: Temperament influences mitochondrial capacity in skeletal muscle from 8. (7th December 2018) - Owen, R; White2, S; Latham, C; Long, C; Randel, R; Welsh, T
Abstract: Muscle mitochondrial capacity and animal temperament have been linked to beef tenderness. We tested the hypotheses that mitochondrial characteristics would be: 1) greatest in temperamental animals; 2) higher in the trapezius than the longissimus dorsi (LD); and, 3) stable as the heifer ages. Samples from both muscle types were collected from the same calm (n=6) and temperamental (n=6) Brahman heifers at 8, 12, and 18 mo of age. Temperament was determined at weaning using pen score and exit velocity. Mitochondrial density and function were measured by colorimetry and mitochondrial capacity was measured utilizing high-resolution respirometry. Data were analyzed using PROC MIXED in SAS (9.4) with repeated measures. Mitochondrial density (citrate synthase activity, CS) increased over time (P < 0.0001) but was similar between temperament and muscle groups. At 12 mo, temperamental heifers had lower mitochondrial function (cytochrome c oxidase activity) compared to calm in the LD (P=0.05) but had similar function between muscle and temperament groups by 18 mo. Integrated (relative to tissue weight) mitochondrial oxidative phosphorylation capacity with complex I substrates (PCI; P=0.012), PCI with complex II substrates (PCI+II; P=0.008), electron transport system capacity (ECI+II; P=0.002), and ECII (P=0.013) were higher in trapezius than LD for calm heifers at all ages, but were similar between muscle groups in temperamental heifers. While unaffected by temperament, intrinsic (relative to CS activity) PCI (P < 0.0001), PCI+II (P=0.0004), ECI+II (P < 0.0001), and ECII (P=0.001) were higher in the trapezius than the LD. Fractional control of CI+II increased from 12 to 18 mo in the trapezius of calm (P=0.035) and the LD of temperamental heifers (P=0.038) but was unchanged by age in the LD of calm and trapezius of temperamental heifers. Calm, but not temperamental, heifers had higher integrative mitochondrial capacity in the trapezius compared to the LD muscle from 8 through 18 mo of age.